Pendekatan One-Health dalam Perang Melawan COVID-19 - Ilyu Ainun Najie; Nur Mufidah Wulan Sari; Trias Mahmudiono (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to find a perspective of the One-Health approach that can be applied in urban areas. The method used is a Scooping review using PRISMA guidelines. The analysis included relevant articles from several scientific databases such as Elsevier, Science Direct, and Scopus. Inclusion and exclusion criteria were used to explore the practice of a one-health approach in urban areas. The research results show that this study provides a One-Health approach that must be considered and can be applied in urban areas. Metropolitan areas with high population mobility are supported by facilities that enable various sectors to support each other in implementing One-Health. Integrated interprofessional collaboration can address the determinants of infectious diseases in humans, animals, and the environment. This study concludes that the One-Health approach is an appropriate mitigation strategy to prevent outbreaks of infectious diseases in urban areas. Keywords: COVID-19, One-Health, Urban